Perbandingan Kinerja Keuangan Koperasi Konvensional Dan Koperasi Syariah Di Kota Bandar Lampung - Nurmala Nurmala; Damayanti Damayanti; Eksa Ridwanysah; Destia Pentiana (Jurnal Ilmiah ESAI, 2018)
There are 740 cooperatives registered in Bandar Lampung, but more than 50% aresuspended. Of these, only a few are actively reporting their financial performance in the formof complete financial statements. Therefore the author assumes that it is important to analyzethe comparison financial performance of conventional cooperative and of Islamiccooperatives in the city of Bandar Lampung. The overall financial performance ofcooperatives is assessed based on the regulation of the State Minister for Cooperatives andSmall and Medium Enterprises of Republic of Indonesia Number: 14 / PER / M.KUKM / XII /2009. The assessment of cooperative health includes capital, quality of productive assets,management, efficiency, liquidity, independence and growth, and cooperative identity. Toassess the financial performance of sharia cooperatives is based on the regulations of theMinister of Cooperatives and Small and Medium Enterprises No. 35.3 / Per / M.KUKM / X /2007. In addition to cooperative health assessments covering capital, quality of productiveassets, management, efficiency, liquidity, independence and growth, and identity ofcooperatives, there is an assessment of compliance with Islamic principles. The objects in thisstudy are cooperatives that actively reported their finances to the cooperative service in 2015and 2016. There are 24 conventional and sharia cooperative financial reports analyzed.Based on the analysis, the financial performance of conventional cooperatives gets a finalscore of 67.15 while the sharia cooperative gets the final score amounting to 74.13. The valueindicates that conventional cooperatives and Islamic cooperatives are equally healthy.Nevertheless, it can be said that the financial performance of Islamic cooperatives is betterthan that of conventional cooperatives.